The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1750-3841.16289
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of toxicological safety evaluation in acute and 28‐day studies of selenium nanoparticles decorated by polysaccharides from Sargassum fusiforme in Kunming mice

Abstract: The monodisperse and nearly spherical selenium nanoparticles decorated by polysaccharides from Sargassum fusiforme (SFPS-SeNPs) were prepared, characterized, and evaluated in acute and 28-day toxicological safety studies.In the acute toxicity study, mice underwent oral administration of 26.94, 40.28, 60.21, 90.11, and 134.70 mg Se/kg of SFPS-SeNPs for 14 days. In the 28-day study, mice underwent a daily oral administration of 17.75, 8.87, and 4.43 mg Se/kg/day of SFPS-SeNPs, 4.43 mg Se/kg/day of Na 2 SeO 3 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Tang et al (2021) showed that Gracilaria lemaneiformis polysaccharidesselenium nanoparticles (GLPs-SeNPs) had excellent biocompatibility. Furthermore, Zhao et al (2022) showed that Sargassum fusiforme (a type of algae) polysaccharides-selenium nanoparticles (SFPS-SeNPs) can reduce the toxicity of Se, and SFPS-SeNPs improved the stability of SeNPs and exerted the biological activities of SFPS (Wang et al, 2021b). However, there are no studies on APS-SeNPs in the field of agricultural Se-enriched fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al (2021) showed that Gracilaria lemaneiformis polysaccharidesselenium nanoparticles (GLPs-SeNPs) had excellent biocompatibility. Furthermore, Zhao et al (2022) showed that Sargassum fusiforme (a type of algae) polysaccharides-selenium nanoparticles (SFPS-SeNPs) can reduce the toxicity of Se, and SFPS-SeNPs improved the stability of SeNPs and exerted the biological activities of SFPS (Wang et al, 2021b). However, there are no studies on APS-SeNPs in the field of agricultural Se-enriched fertilizers.…”
Section: Introductionmentioning
confidence: 99%